Real-life experience of ledipasvir and sofosbuvir single-tablet regimen among chronic hepatitis C patients in Turkey - Yamazhan, Tansu; Turan, İlker; Ersöz, Galip; Günşar, Fulya; Pullukçu, Hüsnü; Danış, Nilay; Ünal, Nalan G.; Vardar, Rukiye; Oruç, Nevin; Tekin, Fatih; Taşbakan, Meltem; Sipahi, Oğuz R.; et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Ledipasvir (LDV) and sofosbuvir (SOF) as single-tablet regimen (STR) has been approved for treatment of chronic HCV infection (CHC) for treatment-naïve or experienced cirrhotic or non-cirrhotic patients. Our aim was to analyse the effectiveness and safety of 12-24 weeks treatment of LDV/SOF (90mg/400 mg)±ribavirin in a real-life setting in Turkey.Materials and Methods: Between May-Dec 2016, 104 treatment-naïve or experienced adult patients with CHC and with or without cirrhosis (including decompensated cirrhosis) were included in this observational study. Patients were administered LDV/SOF STR± ribavirin once daily for 12 -24 weeks. SVR12 rates and effects of the baseline characteristics on SVR12 rates were assessed.Results: Out of 104 enrolled patients (61.5% female, mean age 62.0 years); 60.6% were cirrhotic, 76.0% previously used peg-IFN, 94.2% had GT1. At the end of the treatment, 77.8% (77/99, no data for 21 patients) had undetectable HCV-RNA and 98.9% (94/95) had SVR12. In the baseline characteristics subgroups, the SVR12 rates varied between 94.4% and 100%, and none of the baseline characteristics had a significant effect on the SVR12 rates. During the study, 6 (5.8%) patients died and none of the deaths was suspected to be related to the LDV/SOF. No treatment-emergent adverse event was reported.Conclusion: In conclusion, LDV/SOF±ribavirin yielded very high SVR12 rates, without any safety or tolerability concern in Turkey. The effectiveness of the LDV/SOF treatment was not affected by the patient demographics or medical characteristics such as fibrosis level, cirrhosis status, previous treatment status, HCV-RNA level or HCV genotype.